Traditionalism of Hadith and Polemics with Ahl al-Ra'yi in the Discourse of Classical Islamic Law in the Early 9th Century - Moh Muhlisin; Dzaky Fawwaz Ijlal (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
In the 9th Century, a polemic arose between the traditionalism of hadith and the rational approach of Ahl al-Ra'yi in the early development of classical Islamic law. This study departs from the fact that the expansion of Islamic territory and increasingly complex social changes have given birth to various new legal problems that do not always exist in the Qur'an and Sunnah. This condition encourages scholars to perform ijtihad with two main tendencies, namely ahl al-Ra'yi and Ahl al-Hadith. Ahl al-Hadith places the hadith of the Prophet and the narration of the early generations as the main source of law and is careful in using reason. On the other hand, Ahl al-Ra'yi relies more on rational reasoning, qiyas, and ijtihad. This research uses a qualitative method with a literature study approach, by examining classical works and contemporary scientific studies. The results of the study show that the difference between Ahl al-Hadith and Ahl al-Ra'yi is not just a methodological contradiction, but a process of intellectual dialogue that complements each other. This polemic played an important role in forming the basis of the methodology of classical Islamic law and the subsequent development of the fiqh school.